2002
DOI: 10.1021/ic011115m
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Conformer Equilibria in Retro Models of Cisplatin−DNA Adducts As Revealed by Moderately Dynamic (N,N‘-Dimethyl-2,3-diaminobutane)PtG2 Retro Models (G = a Guanine Derivative)

Abstract: Typical cis-PtA(2)G(2) models of key DNA lesions formed by cis-type Pt anticancer drugs are very dynamic and difficult to characterize (A(2) = diamine or two amines; G = guanine derivative). Retro models have A(2) carrier ligands designed to decrease dynamic motion without eliminating any of three possible conformers with bases oriented head-to-tail (two: DeltaHT and LambdaHT) or head-to-head (one: HH). All three were found in NMR studies of eight Me(2)DABPtG(2) retro models (Me(2)DAB = N,N'-dimethyl-2,3-diami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
124
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 25 publications
(133 citation statements)
references
References 93 publications
8
124
0
Order By: Relevance
“…Crystallization of the LHT conformer could also be favored by utilizing neutral pH, at which the phosphates carry a double-negative charge and the LHT rotamer of 5'-GMP adducts has the highest stability relative to the DHT rotamer. [55,58] Under these conditions, the [Pt- 2 ] adduct gives a solution composition of about 75 % LHT and only 25 % DHT. This strategy proved to be successful and allowed us to grow X-ray-quality crystals containing the LHT conformer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Crystallization of the LHT conformer could also be favored by utilizing neutral pH, at which the phosphates carry a double-negative charge and the LHT rotamer of 5'-GMP adducts has the highest stability relative to the DHT rotamer. [55,58] Under these conditions, the [Pt- 2 ] adduct gives a solution composition of about 75 % LHT and only 25 % DHT. This strategy proved to be successful and allowed us to grow X-ray-quality crystals containing the LHT conformer.…”
Section: Discussionmentioning
confidence: 99%
“…Structural models with both 5'-GMP nucleo-A C H T U N G T R E N N U N G tides in the anti conformation suggested that the 5'-phosphates are directed toward the cis amines in the DHT conformer and toward the cis nucleotide in the LHT conformer. Therefore, phosphate interactions with the cis amine (hydrogen-bond interaction) and with the platinum core (electrostatic interactions) will favor the DHT conformer, whereas phosphate interactions with the cis guanine (hydrogen-bond interaction with cis-5'-GMP N1H) [55][56][57][58] will favor the LHT conformer. However, even for those cases in which our choice of carrier ligand restricted the rotation about the PtÀN7 bond, these adducts are rendered very dynamic by rapid motions involving rotation about the N9 À C1' and the C4' À C5' bonds, and interchange among a very broad range of sugar puckers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These interactions have been grouped into three classes: FFC, SSC and FSC. [21][22][23] FFC (first-to-first sphere communication) involves internucleotide and nucleotide-amine interactions close to the metal center (e.g., the dipole-dipole interaction between cis-guanines, and hydrogen-bond formation between the guanine O6 atom and NÀ H of the cis-amine). SSC (second-to-second sphere communication) involves interactions far from the metal center and between cis-nucleotides (i.e., the hydrogen-bond interaction between the phosphate of a nucleotide and the N1 À H group of the cis-guanine).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, FSC (first-to-second sphere communication) involves interactions between residues, one far from (nucleotide) and the other close to (cis-amine) the metal center (i.e., the hydrogen-bond interaction between the 5'-phosphate of a nucleotide and the NÀH group of the cis-amine). [23] We have focused on highly dynamic [Pt(dach)G 2 ] complexes. NMR spectroscopy is not useful for elucidating the interligand interactions due to fast interconversion between rotamers.…”
Section: Introductionmentioning
confidence: 99%